Results of Treatment of Grades IV and V Vesicoureteral Reflux with Endoscopic Injection of Polyacrylate Polyalcohol Copolymer - Soria, Ricardo; Vagni, Roberto L.; Benmaor, Cesar; Ormaechea, María N.; Moldes, Juan M.; De Badiola, Francisco I. (Frontiers in Pediatrics, 2013)
Purpose: Here we report the results of a review of a prospectively maintained database of the use polyacrylate polyalcohol copolymer (PPC) injection to correct grades IV and V VUR. Materials and Methods: All children with grades IV and V primary VUR that presented with febrile urinary tract infection while on prophylaxis, in a 3-year period, were treated with a sub-ureteral injection of PPC. Institutional ethical approval was obtained. Exclusion criteria were incomplete bladder emptying documented on videourodynamic study, ureteral duplication, paraureteral diverticula, and poor ureteral emptying observed during fluoroscopy and previous open surgical or endoscopic treatment. Pre- and post-operative evaluation included urinalysis, renal and bladder ultrasonography, DMSA scan, and videourodynamic studies. Results: Thirty-three children [36 renal units (RU)] were included with a median age of 57 months (range 7–108). There were 18 boys and 15 girls. Thirty RU had grade IV and 6 grade V VUR. Median follow-up time was 32 months (range 7–58). Reflux was cured in 32/36 RU with the first injection, but another two patients were reimplanted because of dilatation. Complications included early urinary tract infection in seven children, transient lower urinary tract symptoms in five children. Progressive ureteral dilatation was noted in four children and was treated with insertion of a double J stent. Two of these children eventually required an ureteroneocystostomy. Conclusion: The use of PPC to treat grades IV and V vesicoureteral reflux in young children has an overall success rate of 83.3%. Persistent ureteral dilatation was present in 11% associated with high injection volume. Future studies will attempt to maintain a high success rate reducing the volume of injection and the incidence of dilatation.